2013
DOI: 10.1093/toxsci/kft247
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Polymyxin-Induced Nephrotoxicity With Next-Generation Urinary Kidney Injury Biomarkers

Abstract: Despite six decades of clinical experience with the polymyxin class of antibiotics, their dose-limiting nephrotoxicity remains difficult to predict due to a paucity of sensitive biomarkers. Here, we evaluate the performance of standard of care and next-generation biomarkers of renal injury in the detection and monitoring of polymyxin-induced acute kidney injury in male Han Wistar rats using colistin (polymyxin E) and a polymyxin B (PMB) derivative with reduced nephrotoxicity, PMB nonapeptide (PMBN). This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…Lycopene has been shown to interact with ROS and thereby to prevent ROSinduced tissue and cellular damage (35). Consistent with previous studies, we revealed that colistin-induced nephrotoxicity is associated with significantly increased MDA levels and a concomitant decrease in the levels of antioxidant enzymes CAT, SOD, and GSH (Table 2) (16,18,60,61). In the present study, lycopene treatment restored the levels of all of these biomarkers to the normal range observed in the untreated control group (Table 2), confirming its nephroprotective effect.…”
Section: Discussionsupporting
confidence: 92%
“…Lycopene has been shown to interact with ROS and thereby to prevent ROSinduced tissue and cellular damage (35). Consistent with previous studies, we revealed that colistin-induced nephrotoxicity is associated with significantly increased MDA levels and a concomitant decrease in the levels of antioxidant enzymes CAT, SOD, and GSH (Table 2) (16,18,60,61). In the present study, lycopene treatment restored the levels of all of these biomarkers to the normal range observed in the untreated control group (Table 2), confirming its nephroprotective effect.…”
Section: Discussionsupporting
confidence: 92%
“…6,7 Polymyxin B has well-documented toxicity in humans. 18 Protamine has demonstrated toxicity as well, including anticoagulant effects in the absence of heparin 19,20 and the ability to precipitate fibrinogen at high concentrations. 21 Cationic PAMAM dendrimers also interact with and precipitate fibrinogen in solution, 9 which was confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical use of polymyxins was considerably reduced in the early 1970s due to concerns about nephrotoxicity (2)(3)(4). Despite being available for decades, the correlation between the pharmacokinetics and toxicodynamic profiles of polymyxin B is still not thoroughly understood.…”
mentioning
confidence: 99%